Infant learning platform using arduino (project 1) - Ngai, Hei Chak (Nanyang Technological University, 2020)
Effective early childhood development is crucial for the healthy development of infants’ brain and body functions, which allows them to achieve strong physical, mental and emotional health on their journey to adulthood. Language development is one key area of development, as it allows them to communicate and empathise with others. Language also supports cognitive and social growth. Infants usually learn about language through parents reading books, picture cards or word games. However, such methods are often expensive and need to be replaced as the infant grows older. Hence, this project aims to create a customisable learning platform to teach infants basic words, alphabets and their pronunciation. This report dictates the creation of a customisable infant learning platform, using Arduino technology, to teach children language in the form of alphabets, simple words and pronunciation. The platform will be in the form of a game, using various sensors and displays. The goal of the project would be to create an affordable, customisable and interactive game for infants to learn, play and interact with their parents.